PERAN KEGIATAN EDUKATIF KKN DALAM MENINGKATKAN PEMAHAMAN HIDUP SEHAT MELALUI PROGRAM MEMBACA CERITA ANAK DIGITAL BERBASIS FLIPBOOK - Evi Dalilah; Najma Zahiroh; Deka Aprilya; Savira Salsabila; Hilya Musoffa; Decenni Amelia (Jurnal Edukasi Pengabdian Masyarakat, 2026)
Community service through Community Service Programs (KKN) is a form of implementation of the Tri Dharma of Higher Education, aimed at helping address educational issues in the community. This program is motivated by the low literacy, numeracy, and understanding of clean and healthy living behaviors among elementary school children, as well as the suboptimal use of digital learning media. This research employed a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. The program was implemented in Harapan Jaya Village, Bekasi City, through learning assistance activities using digital Flipbook-based children's stories, health education, numeracy strengthening, and activities to develop students' creativity. The results of the activities showed an increase in students' understanding of clean and healthy living, an increased interest in reading through digital media, and the development of numeracy skills through interactive and enjoyable learning. This KKN program is expected to have a sustainable positive impact and serve as an example of community service implementation in the field of elementary education.